Implementation of Continuous Improvement in Governance Public Administration: A Study of the Bojong Village Government Bungbulang District, Garut Regency - Lukman Nulmunir; Aip Zaenal Mutaqin; Mulyaningsih; Susniawati (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Bojong Village, located in Bungbulang District, Garut Regency, has religious tourism potential in the form of the Kandangwesi site, which holds strong historical, spiritual, and cultural value for the local community and pilgrims from various regions. This potential opens up opportunities for development as a religious tourism village that can encourage local economic growth and improve community welfare. However, the development process still faces several problems, including weak tourism management institutions, limited human resource quality, suboptimal coordination between stakeholders, and limited supporting facilities and infrastructure. These conditions demonstrate the importance of implementing collaborative governance involving various actors in village tourism management. This study aims to analyze the development of the Kandangwesi Religious Tourism Village through the perspective of multi-actor collaborative governance. The study used a qualitative approach with a descriptive qualitative research type. Data collection was conducted through in-depth interviews, field observations, and documentation studies involving informants from the village government, the Garut Regency Tourism Office, tourism managers, religious leaders, the local community, and micro and small business actors. The results show that the development of religious tourism villages has involved various actors, but the collaboration patterns formed are still informal. The village government acts as a facilitator and policy director, tourism managers as technical implementers, religious leaders as guardians of spiritual values, local communities as primary supporters of tourism activities, and business actors as drivers of economic activity. Barriers to collaboration include budget constraints, low tourism human resource capacity, weak institutional coordination, and limited infrastructure. Meanwhile, development opportunities are supported by strong local religious and cultural values, high community support, and a relatively stable pilgrimage tourism market potential. Based on these findings, it can be concluded that the implementation of multi-actor collaborative governance plays a strategic role in realizing the development of sustainable religious tourism villages, thus requiring strengthening collaborative institutions, increasing the capacity of actors, and clarifying the division of roles in the future management of Kandangwesi Religious Tourism. Keywords: Collaborative Governance, Multi-Actor, Religious Tourism Village, Village Tourism.